POTENSI SAMPAH UNTUK PEMBANGKIT LISTRIK TENAGA SAMPAH (PLTSa) BERBASIS METODE REGRESI LINIER BERGANDA - Rahmawati, Innieke Ulya; Haddin, Muhammad; Suhartono, Suhartono (Jurnal Teknik Informatika UNIKA Santo Thomas, 2023)
This study discusses the potential prediction of the possibility of developing a waste power plant in Jepara Regency. The demand forecasting model is determined based on input population data, waste volume and electricity demand in Jepara Regency in 2012-2021. Regression analysis is an analysis that aims to determine the most appropriate model for data pairs and investigate the relationship between two or more variables. The results of the study show that Multiple Linear Regression is capable of analyzing the potential of a Waste Power Plant (PLTSa). Based on its significance value, the population variable affects electricity consumption, but the waste volume variable does not significantly affect electricity consumption. MAPE forecasting a population of 0.15%. Forecasting the volume of waste is 15.37%, and electricity consumption is 0%. Utilization of organic waste using direct combustion or incineration technology is capable of producing output power from generators within 25 years (2022-2048) which can only support 45% of electricity consumption in Jepara Regency.